Validity of Sale and Purchase Binding Agreement in Pre-Project Selling Transaction - Aurellia, Clara Sabrina; Winanti, Atik (Jurnal Ius Constituendum, 2024)
This research aims to analyze the legal aspects of the PPJB, identify factors that affect its validity, and evaluate the legal protection provided to consumers. In recent years, there have been increasing cases of consumers being harmed when buying property on a pre-project selling basis because the PPJB often disregards consumer rights according to applicable laws, thus favoring developers. This research is important to contribute to the development of regulations that are more comprehensive and provide legal certainty for all parties involved in pre-project selling property transactions. This topic has not been comprehensively addressed in previous studies. The research method used in this study is normative legal research with a statutory approach, and the data collection technique employed is a literature study. The results of this research indicate that developers must fulfill all existing requirements before selling property through pre-project selling, which should be formalized in a PPJB executed before a notary or in an informal PPJB. The PPJB is binding, and the parties must comply with its contents. Developers are obligated to compensate consumers if their actions have caused harm.